(untitled) (Razi Medical Journal, 2025)
The global surge in diabetes and obesity underscores the role of adipokines. Asprosin disrupts glucose homeostasis, while nesfatin-1 may offer protective effects. This study investigated their serum levels in poorly controlled T2DM and associations with hyperglycemia and obesity. The study included 110 type 2 diabetes patients and 70 healthy controls, aged 40–70 years. Fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c) were measured using the Roche Cobas Integra 400 Plus. Serum asprosin and nesfatin-1 levels were quantified by ELISA, and body mass index (BMI) was calculated as weight/height². T2DM patients exhibited significantly higher serum levels of asprosin and nesfatin-1 compared to controls (p < 0.001). A significant positive correlation was observed between asprosin and nesfatin-1, as well as between nesfatin-1 and disease duration (p = 0.01). Serum asprosin was strongly associated with glucose levels, whereas neither biomarker showed a significant correlation with BMI. Elevated asprosin and nesfatin-1 levels in poorly controlled T2DM patients contribute to disease mechanisms. Increased nesfatin-1 represents a compensatory mechanism to mitigate insulin deficiency, highlighting its potential as a predictive biomarker.